Effects of air abrasive decontamination on titanium surfaces: A systematic review of in vitro studies. (5th March 2019) - Moharrami, Mohammad; Perrotti, Vittoria; Iaculli, Flavia; Love, Robert M.; Quaranta, Alessandro
Abstract: Background: Air abrasion (AA) is one of the decontamination methods that have demonstrated promising results in treating peri‐implant diseases. Purpose: This systematic review aimed at evaluating the in vitro effect of AA on surface change, cleaning efficacy, and biocompatibility of titanium surfaces and at comparing it with other decontamination methods. Materials and Methods: A comprehensive search was conducted up to April 2018 using PubMed, Scopus, and Google Scholar databases to identify studies on the decontamination effect of AA. All types of titanium surfaces, abrasive powders, contaminated surfaces, and measuring methods were included. Results: Overall, 1502 articles were identified. After screening the titles and abstracts, and carefully reading the full‐texts, 48 articles published between 1989 and 2018 were selected. AA was considered almost safe, particularly for the nonmodified surfaces. Nevertheless, harder powders such as sodium bicarbonate tended to damage the surface more than glycine. AA resulted in surface change similar to plastic curettes and Er: YAG lasers. Regarding the cleaning efficacy, there was no significant difference between glycine and sodium bicarbonate, but different mixtures of calcium phosphate, hydroxyapatite, and erythritol were superior to glycine. AA was superior or equal to all other decontamination methods in cleaning. Regarding biocompatibility, AA was more successful in preserving biocompatibility for noncontaminated surfaces compared with contaminated surfaces and when used with erythritol and osteoinductive powders. Conclusions: AA can efficiently remove contamination without serious damage to the surface. The main drawback of the AA method seems to be its limitation in restoring the biocompatibility of the surface.